Electrospun fibers of poly(butylene succinate–co–dilinoleic succinate) and its blend with poly(glycerol sebacate) for soft tissue engineering applications. (August 2016) - Liverani, Liliana; Piegat, Agnieszka; Niemczyk, Agata; El Fray, Miroslawa; Boccaccini, Aldo R.
Graphical abstract: Highlights: Synthesis of new copolymer poly(butylene succinate-dilinoleic succinate) has been obtained. Optimized electrospun fibers obtained for neat copolymer and blend with poly(glycerol sebacate). A feasibility study about blend spun fibers functionalization has been performed. Abstract: A new copolymer poly(butylene succinate-dilinoleic succinate) (PBS-DLS) has been successfully synthesized and its suitability for the fabrication of electrospun fiber mats has been investigated for the obtaining both electrospun scaffolds of neat PBS-DLS and also in blend with poly(glycerol sebacate) (PGS). After optimizing the electrospinning process for both neat and PGS/PBS-DLS (ratio 1:2) blend materials, homogeneous fiber mats have been obtained with an average fiber diameter of 2.5 ± 0.5 μm and 2.0 ± 0.2 μm, for neat and blend mats, respectively. Mechanical properties and degradation behavior in PBS were investigated to evaluate their suitability for soft tissue engineering applications. A feasibility study of the obtained electrospun mats functionalization was performed and positive results were obtained, demonstrating the versatility and suitability of PGS/PBS-DLS electrospun fibers as candidate for soft tissue engineering applications.